Landscape Change Analysis: Ecosystem Services in the Peri-urban Agriculture of Bangkok - Likitswat, Fa; Sahavacharin, Alisa (Journal of Architectural/Planning Research and Studies (JARS), 2022)
Over the past decades, Bangkok peri-urban has been transformed from agricultural villages to urban development communities. Within the flat terrain and poor drainage characteristic of Chao Phraya Lower Floodplain, peri-urban agricultures are considered to be one of landscape patches and areas that creating and adding ecosystem services and values for mega urban areas. The significant loss of agricultural landscape of Bangkok peri-urban means that the loss of seasonal water retention areas, productive landscapes, as well as habitat for urban wildlife. This research classifies and analyzes landscape transformations especially agricultural landscape structures and functions of eight selective sites surrounded by the urban fringe of Bangkok. By tracing over the landscape change patterns backs form 1952 to 2018, the study areas include; 1) Rangsit Klong Sam and Klong Si, Pathumthani 2) Bang Kradi, Patumthani, 3) Lum Lukka Klong Hok Wa, Patumthani, 4) Klong Chorakea Noi and Klong Lat Krabang, Bangkok, 5) Bang Pla, Samut Prakarn, 6) Kok Kham, Samutsakorn, 7) Tha Mai, Samutsakorn, and 8) Klong Mahasawat, Nakorn Pathom. It is also critical linking and discussing on the ecosystem functions and services toward sustainable landscape management. This paper concludes the research gap between the lack of policies to practices for promoting the ecosystem services linking to the preserving and focusing on peri-urban agriculture landscape of Bangkok.